The influence of particle surface oxidation treatment on microstructure and mechanical behavior of 3D-SiCp/A356 interpenetrating composites fabricated by pressure infiltration technique - Jianning Lu; Juan Wang; Yingfei Lin; Kaihong Zheng; Zhuo Tian; Peixian Han (Journal of Materials Research and Technology, 2023)
In this work, the 3D-SiCp/A356 composites with interpenetrating microstructure were prepared by pressure infiltration of A356 aluminum alloy into a porous 3D-SiC ceramic preform, which served as reinforcement. The effects of the surface oxidation treatment of the SiC particles on microstructure, thermal expansion coefficient, and bending strength of as-fabricated composites were investigated. The results revealed that the initial structure of the 3D-SiC ceramic preform could be retained after pressure infiltration, the pores of the preform were filled with A356 aluminum alloy, and the particles were uniformly distributed in the A356 matrix alloy. The thermal expansion coefficient of the SiC/A356 composite reinforced by oxidized SiC particles was lower than that of the unoxidized SiC particle-reinforced composite. It increased with increasing temperature for both, eventually reaching maxima at 420 °C and 350 °C, respectively, and decreased thereafter. However, a rapid decrease in the thermal expansion coefficient was evident at 565 °C because of the over-burning of the A356 aluminum matrix. In particular, the surface oxidation treatment of SiC particles changed the nature of bonding between SiC and Al, which reduced the strength of the composites. As a result, the bending strength of the unoxidized SiC particle-reinforced composite was approximately twice that of the oxidized SiC particle-reinforced composite. Additionally, the bending strength values of the SiC–Al showed an obvious anisotropic behavior. The bending strength measured by loading parallel to the infiltration direction was 2.5 times larger than that of a perpendicular loading.